CONCEPT OF UMMAH IN THE AL-QUR’AN - Bakar, Fatum Abu (Hunafa: Jurnal Studia Islamika, 2020)
In the discourse of Koran studies in the West, the term ummah is often associated with religious and political communities. In its aftermath, this association has implications for understanding the ummah's vocabulary texts in the Qur'an. Toshihiko Izutsu, an Islamic scholar from Japan, introduced a new method of interpreting the Qur'an, namely a linguistic approach based on semantic theory. Izutsu uses the term ummah in the Qur'an as an issue he examines with this approach. Interpretation of the term ummah with a semantic approach is considered capable of presenting a variety of insights which he calls the Qur'anic weltanschauung. This article describes the framework of the semantic approach applied by Izutsu. The use of synchronic and diachronic approaches, as implemented by Izutsu, should be considered by scholars of the Qur'an, especially in presenting various insights in terms that have social implications.